Efektivitas Pengawasan Internal Pendamping PKH Dalam Penyaluran Bantuan Sosial di Desa Telaga Suka - Azira Wahyu Armanda (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this study was to determine the effectiveness of the companion in the implementation of the family of hope program in the distribution of social assistance in the village of Telaga Suka. This study uses a qualitative approach. Informants were determined by purposive sampling technique. The results showed that the facilitator in implementing PKH in Telaga Suka village was effective. Understanding the program, PKH facilitators have been able to clearly understand the tasks and functions that must be carried out, Timeliness is good enough from the time of program implementation to the end of the program in accordance with predetermined provisions. and the achievement of the goals of distributing aid funds so far has gone very well, the achievement of the objectives carried out by PKH facilitators has met the targets, as can be seen from the success of PKH facilitators in empowering the poor.